Kritik Tafsir Ayat-Ayat Pendidikan terhadap Pendidikan Segregasi, Pendidikan Inklusif, dan Pendidikan Integrasi (Studi Pendidikan di Perguruan Tinggi Yogyakarta) - Aris Nurlailiyah (AN NUR: Jurnal Studi Islam, 2015)
Qur’an verses with making Islam is rich with theory. The theory contained in it made the quote by scholars of Islamic education as the basis of Islamic education. The theory brought criticism of the interpretation that exists in Indonesia had a great concept. The concept of exigesis Quran examines on every problem raised in the living Qur’an. Exsigesis of the living Qur’an about education resulted in Islamic education experts interpret the education in his divided into three concept of education. Three concepts that used educational practitioners make exsigesis al-Quran becomes problematic. This paper tried to see criticism of the interpretation that exists in living Quran on the concept of education which used educational practitioners in applying the model of learning